The Use of Semantic Mapping Strategy to Improve Students’ Skill in Writing Descriptive Texts: a Classroom Action Research (CAR) - Nurul Akbar; Yulitriana (General English Education, 2022)
Writing is a complicated skill should be mastered by students as it requires some knowledge related the purpose of the text, generic structure, and language features as well as the skills to organize the ideas and information in a logical way by keeping the unity and coherence of the text, so the piece of writing will be easily understood by the readers. Therefore, some students at the tenth grade of SMK Muhammadiyah Karangampel experience difficulties in writing a text, especially in writing descriptive texts. In order to improve the students’ skills in writing descriptive texts, the teacher applies semantic mapping strategy. The result shows that there is improvement in students’ scores after the treatment as semantic mapping technique facilitates their needs to brainstorm and organize ideas and information.